2021
DOI: 10.1136/bmjopen-2020-041734
|View full text |Cite
|
Sign up to set email alerts
|

Excess burden of age-associated comorbidities among people living with HIV in British Columbia, Canada: a population-based cohort study

Abstract: ObjectivesAs people living with HIV (PLWH) live longer, morbidity and mortality from non-AIDS comorbidities have emerged as major concerns. Our objective was to compare prevalence trends and age at diagnosis of nine chronic age-associated comorbidities between individuals living with and without HIV.Design and settingThis population-based cohort study used longitudinal cohort data from all diagnosed antiretroviral-treated PLWH and 1:4 age-sex-matched HIV-negative individuals in British Columbia, Canada.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…We found higher rates of not only comorbidities among LTHS, but also particular diseases: COPD, history of cancer, osteoarthritis, depression, and other psychiatric disorders. COPD is strongly linked to smoking and more prevalent among people with HIV than in general population [ 20 ]; it consumes a great deal of resources, and has been demonstrated to negatively impact the QOL of people with HIV [ 21 ]. COPD was twice as prevalent within LTHS as in the HAART-era group, and LTHS were more likely to be active smokers.…”
Section: Discussionmentioning
confidence: 99%
“…We found higher rates of not only comorbidities among LTHS, but also particular diseases: COPD, history of cancer, osteoarthritis, depression, and other psychiatric disorders. COPD is strongly linked to smoking and more prevalent among people with HIV than in general population [ 20 ]; it consumes a great deal of resources, and has been demonstrated to negatively impact the QOL of people with HIV [ 21 ]. COPD was twice as prevalent within LTHS as in the HAART-era group, and LTHS were more likely to be active smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Second, more than 50% of PLWH in Oregon and the United States are over age 50 [3]. Third, PLWH are more likely to experience comorbid medical conditions and experience them at a younger age compared to those without HIV [4]. Fourth, PLWH are more likely to experience social and economic disadvantage than those without HIV [5] and this disadvantage is associated with a greater risk of COVID-19 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In striking contrast, in this study the median age was 50.5 years, signi cantly lower than the studies previously described, and raised considerable probability that the young age of onset could relate directly to HIV infection. Notably, a Canadian study showed [11] that the median age of HIV infected patients was 40 years old.…”
Section: Resultsmentioning
confidence: 99%